THE INFLUENCE OF EASE OF USE AND TRANSACTION SECURITY ON TRANSACTION SATISFACTION THROUGH THE INTENSITY OF QRIS (QUICK RESPONSE INDONESIAN STANDARD) USAGE AMONG STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, STATE UNIVERSITY OF JAKARTA - Kurniawan, Moh Irfan Dwi Kurniawan; Adeqo, Rizkitito Adeqo; Usman, Osly Usman (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
Abstract. This study aims to analyze the influence of ease of use and transaction security on transaction satisfaction through the intensity of QRIS usage among students of the Faculty of Economics and Business at Universitas Negeri Jakarta. As digital financial technology advances, QRIS (Quick Response Code Indonesian Standard) has emerged as a practical and efficient payment system widely adopted in academic environments. The research employed a quantitative approach using Structural Equation Modeling (SEM) with SmartPLS 4 and collected data from 112 respondents. The results reveal that ease of use significantly affects both usage intensity (β = 0.608, p < 0.001) and transaction satisfaction (β = 0.586, p < 0.001), while transaction security significantly influences usage intensity (β = 0.292, p = 0.002) but does not significantly affect satisfaction (β = 0.051, p = 0.689). Interestingly, transaction satisfaction does not significantly mediate the relationship between ease of use or security and usage intensity. The findings indicate that students are more driven to use QRIS frequently due to its practical and secure nature rather than emotional satisfaction. This research contributes to understanding user behavior in digital payments and provides strategic recommendations for improving QRIS adoption among youth. Keywords, QRIS, ease of use, transaction security, transaction satisfaction, usage intensity, digital payments, university students.